The effect of acid modification on adsorption of ortho-nitrophenol from aqueous solution by multi wall carbon nanotubes and conical carbon nanofibers: characterization, modelling and performance - Asmaly, Hamza A.; Kabbashi, Nassereldeen Ahmed; Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir; Sulaman, Adam (IIUM Press, 2023)
This study examined the absorption of ortho-nitrophenol onto Conical carbon nanofibers (CCNFs) and multi-wall carbon nanotubes (MCNTs). The properties of the CNTs and CNFs were analyzed using various techniques such as X-ray diffraction, scanning electron microscopy, Fourier-transform infrared spectroscopy, Brunauer-Emmett-Teller for surface area analysis, Energy dispersive X-ray spectroscopy and transmission electron microscopy. The study investigated the effectiveness of hydrochloric acid-activated the surface of both CNTs and CNFs in removing 2-NitroPhenol ions from an aqueous solution. The Central-Composite design of RSM was employed to study the impact of solution pH, agitation speed, adsorption time, and adsorbent dosage on the adsorption process and then optimize these parameters for the removal of 2NP. The results of the optimization revealed that the best conditions for removing 2-Nitro Phenol were pH 6.6, for 68.0 minutes, at 80 rpm agitation and 108mg of adsorbent. Additionally, the effect of the initial concentration was evaluated, and the adsorption capacity of the nano-activated carbon adsorbents was calculated. The study found that multi-wall carbon nanotubes (MWCNTs) with a high surface area are more effective than Conical carbon nanofibers (CCNFs) in reducing 2-NP from an aqueous solution, making MWCNTs a potentially useful material in the fight against environmental pollution.